Pengembangan Bola Karet Alat Pengukur Kekuatan Otot Tangan - Eny Erlinda Widyaastuti; Erni Chaerani; Husman Husman; Eko Yudo (Journal of Telenursing (JOTING), 2023)
This study aims to test the right rubber ball for measuring hand muscle strength. This research method was carried out using a quasi-experimental design. The results showed that the value of count (Pearson Product Moment Correlation) > r-table was 0.176. The reliability test results on the three right and left-hand measuring instruments were > 0.6 with a Cronbah's Alpha value of 0.920 > 0.6. In conclusion, testing the validity and reliability of rubber balls on muscle strength measuring devices with sizes of 7 cm, 8 cm, and 9 cm, which was carried out involving 130 respondents, showed valid and statistically reliable results. Keywords: Rubber ball, Hand Muscle Strength, Clinical Assessment